The Indigenous Child Removal System in Canada: An Examination of Legal Decision-making and Racial Bias - Sinclair, Raven (First Peoples Child & Family Review, 2016)
This Indigenous child removal system in Canada has been in operation since the 1950s and has created unprecedented Indigenous child overrepresentation in the child welfare system. While five generations of residential schools and disastrous socio-economic conditions often warrant child welfare involvement, the statistics for Indigenous children in care are so disproportionate that we are called to examine key factors that have created and sustain the system. While history provides a contextual frame for these statistics, examining legislation and legal decision-making in Indigenous child welfare cases sheds light on how legal and racial factors contribute to ongoing Indigenous child removals from families and culture. This article is a call for the Indigenous child removal system to be overhauled and suggests that the recommendations of the Truth and Reconciliation Commission final report can guide us in how that can be achieved.